Imagine the Dog : A Novella - Pinto, Cecilia (Book collections on Project MUSE., 2021)
"Ricky Rudolph believes that he has been called to offer hope and healing to others by impersonating Jesus. But his own life is a complicated mess, including financial difficulties, a pregnant daughter, and a mounting suspicion on the part of law enforcement that he's up to no good"--